The Protective Effect of Platelet Rich Plasma Against Cisplatin-Induced Ototoxicity. Issue 5 (July 2020) - Yurtsever, Kum Nurcan; Baklaci, Deniz; Guler, Ismail; Kuzucu, Ihsan; Kum, Rauf Oguzhan; Ozhamam, Esra Ucaryilmaz; Ozcan, Muge; Dere, Huseyin
Abstract : Abstract: Cisplatin, a pharmacological agent widely used for treating many cancers, may cause serious side effects including ototoxicity, nephrotoxicity, and peripheral neuropathy. The present study aimed to investigate whether platelet-rich plasma (PRP) protects against cisplatin ototoxicity. Eight rats (16 ears) were divided into 2 groups: control group (4 rats, 8 ears) that received intratympanic saline and study group (4 rats, 8 ears) that received intratympanic PRP. Cisplatin (10 mg/day intraperitoneally) or vehicle was administered 2 times per day to the animals. Auditory brainstem responses were recorded preoperatively and postoperatively on day 4 and at week 3. The authors compared the morphological appearances of spiral ganglion cells and the organ of Corti and the density of spiral ganglion cells between treatment groups. The number of outer hair cells in the organ of Corti significantly decreased in the control group compared with that in the PRP group. Although no statistically significant difference was observed between the groups regarding ABR thresholds on day 4 ( P = 0.083, a statistically significant difference was observed between groups at week 3 ( P = 0.038). Our results suggest that PRP can prevent cisplatin-induced ototoxicity. Abstract : Supplemental Digital Content is available in the text